Facile fabrication of nitrogen doped carbon from filter paper for CO2 adsorption. (15th November 2019) - Cui, Hongmin; Xu, Jianguo; Shi, Jinsong; Yan, Nanfu; Liu, Yuewei
Abstract: The preparation and application of heteroatom doped carbons have attracted lots of attention in the past years. In the current work, a facile synthesis of nitrogen doped carbon with filter paper as the carbon source and urea as the nitrogen source was presented. Filter paper was first impregnated with urea solution, and was then carbonized and activated. The carbons' physical and chemical properties were studied. For the application in CO2 adsorption, impacts from porous characteristics and nitrogen doping were discussed and differentiated. The results suggested that nitrogen doping was beneficial to the improvement of CO2 uptake, but suitable porous properties were the most important factors. Nitrogen doping showed more significant effects on enhancing the adsorption heat and selectivity. The research of carbonaceous CO2 adsorbent should focus on nitrogen doped carbons with high porosity. Highlights: Urea loaded filter paper is used as starting material for nitrogen doped carbon. Effects of nitrogen doping and porous structure on CO2 adsorption are studied. CO2 uptake at 273 K and 1 bar reaches 5.12 mmol/g. Nitrogen doping has obvious effects on CO2 adsorption heat and selectivity.